10-Year Evaluation of the First Root Analogue Implant on Humans, Made Using a CT Scan, CAD/CAM and DMLS - Michele Mario Figliuzzi; Domenico Aiello; Carlo Rengo; Luca Parentela; Carlo Mangano (Biomimetics, 2022)
Ten years ago, for the first time in humans, thanks to the DLMS (direct metal laser sintering) technique, we designed, built and inserted an immediate post-extraction custom-made root-analogue implant in Ti-6Al-4v with platform switching. The implant was inserted into the post-extraction socket, respecting the biological width. After 10 years, we wanted to evaluate the dimensional stability of the implant and the eventual crestal bone resorption. The evaluation was performed clinically with periodontal parameters and radiographically by means of an intraoral X-ray with the parallel technique measuring the distance between the base of the bone crest and the implant shoulder. It appears that the implant has maintained dimensional stability of the peri-implant soft tissues, and the crestal resorption is 0 mm. This could represent a step forward to make this experimental method a valid alternative to the current immediate post-extraction implant procedures in use.